MODEL REKLAMASI LAHAN ADAPTIF UNTUK TAMBANG RAKYAT DI KABUPATEN SUMBAWA: STUDI KASUS DAN REKOMENDASI - Welly Nuraga; Sayidatina Hayatuzzahra; Nandhita Suri Kallo; Robby Mardian Safitra; Rita Desiasni (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
income for the local community, also have negative impacts, namely land degradation with numerous abandoned and poorly managed former mining holes. This research aims to provide practical and sustainable recommendations for adaptive reclamation activities in former artisanal mining areas in Area Y, and to serve as a guide for realizing more responsible and sustainable artisanal mining practices. The research was conducted using a qualitative method through the analysis of relevant secondary data. The study results indicate that miners tend to leave former mining holes unreclaimed. This is due to miners' limitations in both technical knowledge and capital, rendering them incapable of carrying out reclamation independently. The impact of these abandoned mining holes has the potential to become a future hazard. The selection of an adaptive land reclamation model focusing on a flexible and participatory approach has proven to be an effective and efficient method for implementing reclamation activities in artisanal mining. Both government and non-governmental agencies can conduct intensive education and training to maximize local community participation for the success of reclamation activities